Effect of AlN nanoparticle concentration in the electrolyte on corrosion resistance and mechanical properties of the electrodeposited composite coatings - M.S. Khan (22047413) (2024)
The impact of corrosion is widespread, affecting structures, equipment, and infrastructure across various industries increasing the maintenance cost and thereby decreasing profit and efficiency. Nickel-based coatings are one of the most tempting options owing to their enhanced mechanical and corrosion-resistant properties. This research aims to develop an innovative solution by incorporating AlN nanoparticles with various concentrations (0.1, 0.2, 0.4, and 0.8 g/L) as reinforcement in the Ni-P electrolyte to develop composite coatings using A36 carbon steel as a substrate through direct current (DC) electrodeposition method. Analytical techniques such as X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy, and electrochemical impedance spectroscopy were employed for the analysis of fabricated coatings. The surface morphology highlights the formation of well defined granural structure with the introduction of AlN nanoparticles into the Ni-P matrix, which leads to the enhancement in both corrosion resistance and mechanical properties. The findings indicate that the concentration of 0.4 g/L exhibits the highest corrosion resistance of 86.6% compared to carbon steel. Furthermore, the coatings displayed improved mechanical strength, with the Ni-P-0.4 g/L AlN composite coating registering the highest hardness at 660 HV0.025. The results propose that Ni-P-AlN composite coatings have the potential to augment the mechanical characteristics and corrosion resistance of metallic substrates, presenting a promising solution for various industrial applications such as water treatment, pipelines, chemical industries, mechanical, marine, aerospace, and oil & gas industries. Other Information Published in: Materials Today Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.mtcomm.2024.108330